Freshwater Macrophytes: A Potential Source of Minerals and Fatty Acids for Fish, Poultry, and Livestock - Kumar, Guddu; Sharma, JaiGopal; Goswami, Ravi Kumar; Shrivastav, Avanish Kumar; Tocher, Douglas R.; Kumar, Neelesh; Chakrabarti, Rina (Frontiers in Nutrition, 2022)
The freshwater macrophytes are abundant in tropical and subtropical climates. These macrophytes may be used as feed ingredients for fish and other animals. The nutritional value of twelve freshwater cultured macrophytes was evaluated in the present study. Significantly higher crude protein (36.94-36.65%) and lipid (8.13-7.62%) were found in Lemna minor and Spirodela polyrhiza; ash content was significantly higher in Hydrilla verticillata, Wolffia globosa and Pistia stratiotes (20.69-21.00%) compared to others. Highest sodium, magnesium, chromium and iron levels were recorded in P. stratiotes. H. verticillata was rich source for copper, manganese, cobalt and zinc; calcium, magnesium, strontium and nickel contents were highest in S. polyrhiza. Selenium and potassium contents were higher in Salvinia natans and W. globosa, respectively. The n-6 and n-3 polyunsaturated fatty acids (PUFAs) contents were significantly higher in W. globosa and Ipomoea aquatica, respectively compared to others. Linoleic and α-linolenic acids were dominant n-6 and n-3 PUFAs. Highest (4.04) n-3/n-6 was found in I. aquatica. The ratio ranged from 0.61-2.46 in other macrophytes. This study reveals that macrophytes are rich sources of minerals, n-6 and n-3 PUFAs.